Impact of Left Ventricular Assist Device Speed Adjustment on Exercise Tolerance and Markers of Wall Stress. Issue 9 (September 2015) - Hayward, Christopher S.; Salamonsen, Robert; Keogh, Anne M.; Woodard, John; Ayre, Peter; Prichard, Roslyn; Kotlyar, Eugene; Macdonald, Peter S.; Jansz, Paul; Spratt, Phillip
Introduction: Left ventricular assist devices are crucial in rehabilitation of patients with end-stage heart failure. Whether cardiopulmonary function is enhanced with higher pump output is unknown. Methods: 10 patients (aged 39 ± 16 years, mean ± SD) underwent monitored adjustment of pump speed to determine minimum safe low speed and maximum safe high speed at rest. Patients were then randomized to these speed settings and underwent three 6-minute walk tests (6MWT) and symptom-limited cardiopulmonary stress tests (CPX) on separate days. Results: Pump speed settings (low, normal and high) resulted in significantly different resting pump flows of 4.43 ± 0.6, 5.03 ± 0.94, and 5.72 ± 1.2 l/min ( P <.001). There was a significant enhancement of pump flows (greater at higher speed settings) with exercise ( P <0.05). Increased pump speed was associated with a trend to increased 6MWT distance ( P = .10); and CPX exercise time (p = .27). Maximum workload achieved and peak oxygen consumption were significantly different comparing low to high pump speed settings only ( P <.05). N-terminal-pro-B-type natriuretic peptide release was significantly reduced at higher pump speed with exercise ( P <.01). Conclusions: We have found that alteration of pump speed setting resulted in significant variation in estimated pump flow. The high-speed setting was associated with lower natriuretic hormone release consistent with lower myocardial wall stress. This did not, however, improve exercise tolerance.